Efficacy and safety of umbilical cord mesenchymal stem cells for the treatment of patients with COVID-19 - Wei, Fengtao; Kong, Dexiao; Li, Tao; Li, Ai; Tan, Yi; Fang, Jinfeng; Zhuang, Xianghua; Lai, Chao; Xu, Weihua; Dong, Hong; Ma, Chengen; Hong, Ke; et al. (Clinics, 2021)
OBJECTIVES: The coronavirus disease (COVID-19) outbreak has catastrophically threatened public health worldwide and presented great challenges for clinicians. To date, no specific drugs are available against severe acute respiratory syndrome coronavirus 2. Mesenchymal stem cells (MSCs) appear to be a promising cell therapy owing to their potent modulatory effects on reducing and healing inflammation-induced lung and other tissue injuries. The present pilot study aimed to explore the therapeutic potential and safety of MSCs isolated from healthy cord tissues in the treatment of patients with COVID-19. METHODS: Twelve patients with COVID-19 treated with MSCs plus conventional therapy and 13 treated with conventional therapy alone (control) were included. The efficacy of MSC infusion was evaluated by changes in oxygenation index, clinical chemistry and hematology tests, immunoglobulin (Ig) levels, and pulmonary computerized tomography (CT) imaging. The safety of MSC infusion was evaluated based on the occurrence of allergic reactions and serious adverse events. RESULTS: The MSC-treated group demonstrated significantly improved oxygenation index. The area of pulmonary inflammation decreased significantly, and the CT number in the inflammatory area tended to be restored. Decreased IgM levels were also observed after MSC therapy. Laboratory biomarker levels at baseline and after therapy showed no significant changes in either the MSC-treated or control group. CONCLUSION: Intravenous infusion of MSCs in patients with COVID-19 was effective and well tolerated. Further studies involving a large cohort or randomized controlled trials are warranted.